Development of a Patient Safety Model in Independent Practice of Midwifery in Bogor Regency, West Java, Indonesia - Nina Herlina; Yudhia Fratidhina; Ambariani; Sri Mulyati; Titin Martini (Indian Journal of Forensic Medicine & Toxicology, 2021)
The concept of patient safety has been developed due to the increased incidence of medical error in Indonesia.Although incidents related to patient safety occurs in health servicessuch as the Independent Practice ofMidwifery or BidanPraktikMandiri(BPM), it has not received enough attention from the stakeholders. Thisresearch discusses the implementationof Patient Safety Model atthe Independent Practice of MidwiferyinBogor District, West Java Province. The research was conducted with mixed method approach, using threewayphase. The first phase is the construction on patient safety goals in BPM by doing focus group discussionon 3 groups and 2 in-depth interviews with 2 informants. The second phase is the model development inthe form of validation based on findings in the first phase. Additionally, phase 2 is done by using crosssectionaldesign of 90 midwives and SEM analysis using PLS. The third phase is conducting a quantitativeevaluation model with pre and post design at 30 BPM which have had training on Patient Safety Model. Thefindings show allvariables (patient safety goals, knowledge, attitudes, motivations, and behaviors related tothe patient safety) are valid in shaping Patient Safety Model. The results on Model application evaluation(phase 3) indicate that the model effective in increasing knowledge (p 0.000), attitude (p 0.000), motivation(p 0.000) and behavior (p 0.001) on patient safety in BPM.